A designação das línguas e sua distribuição para falantes na tríplice fronteira Brasil - Paraguai - Argentina - Azzali, Amanda Castilho (2019)
In this research, we seek to understand the distribution of languages ​​in the enunciative area of ​​the border region of Foz do Iguaçu, in the state of Paraná. This work, since inserted within a Semantics of Enunciation, aims to deal with the relation between languages ​​as a political relation that is given by the way the speakers designate the languages ​​they speak. Therefore, we will approach this question from a political, historical, and social perspective of language. Based on our analyses, we observe the extent to which the distribution of languages ​​in this space - the official languages ​​of the bordering States, the phrases deriving from the linguistic relations, such as the portunhol and jopara, or those of immigrants - is related to the fact that people speak and hear a certain language in their daily life, which authorizes the subject to speak in one or another language in order to understand what each language designates and how they constitute the speakers. Our corpus consists on answers from an interview elaborated for this research and on advertisements found in public spaces in order to observe the functioning and distribution of languages ​​and also to understand, in the enunciative scenes, how the meanings that designate the languages are being constituted in this enunciation space, as a political space. The results of our analyses show us, through the procedures that the speakers operate in the organization of the text in the event of enunciation, such as rewriting and articulation, that the speaker of the border or speaker of a border space functions as a political figure that is mobilized in several languages ​​and, in enunciating, it signifies itself as divided by the languages ​​and positions itself when identifying with the socio-historical conditions in which it is inscribed.